Linear Growth Trajectories, Catch-up Growth, and Its Predictors Among North Indian Small-for-Gestational Age Low Birthweight Infants: A Secondary Data Analysis - Sinha, Bireshwar; Choudhary, Tarun Shankar; Nitika, Nitika; Kumar, Mohan; Mazumder, Sarmila; Taneja, Sunita; Bhandari, Nita (Frontiers in Nutrition, 2022)
Background Low birthweight small-for-gestational-age (SGA-LBW) (birthweight below the 10th percentile for gestational age; SGA-LBW) infants are at an increased risk of poor postnatal growth outcomes. Linear growth trajectories of SGA-LBW infants are less studied in South Asian settings including India. Objectives To describe the linear growth trajectories of the SGA-LBW infants compared with appropriate-for-gestational-age LBW (AGA-LBW) infants during the first 6 months of life. In addition, we estimated catch-up growth (ΔLAZ > 0.67) in SGA-LBW infants and their performance against the WHO linear growth velocity cut-offs. Additionally, we studied factors associated with poor catch-up growth in SGA-LBW infants. Methods The data utilized came from an individually randomized controlled trial that included low birthweight (LBW) infants weighing 1,500–2,250 g at birth. A total of 8,360 LBW infants were included. For comparison between SGA-LBW and AGA-LBW infants, we presented unadjusted and adjusted estimates for mean differences (MDs) or risk ratios (RRs) for the outcomes of length, linear growth velocity, length for age z-score (LAZ) score, and stunting. We estimated the proportion of catch-up growth. Generalized linear models of the Poisson family with log links were used to identify factors associated with poor catch-up growth in SGA-LBW infants. Results Low birthweight small-for-gestational-age infants had a higher risk of stunting, lower attained length, and a lower LAZ score throughout the first 6 months of life compared with AGA-LBW infants, with differences being maximum at 28 days and minimum at 6 months of age. The linear growth velocity in SGA-LBW infants compared with AGA-LBW infants was significantly lower during the birth–28 day period [MD −0.19, 95% confidence interval (CI): −0.28 to −0.10] and higher during the 3- to 6-month period (MD 0.17, 95% CI: 0.06–0.28). Among the SGA-LBW infants, 55% showed catch-up growth for length at 6 months of age. Lower wealth quintiles, high birth order, home birth, male child, term delivery, non-exclusive breastfeeding, and pneumonia were associated with the higher risk of poor catch-up in linear growth among SGA-LBW infants. Conclusion Small for gestational age (SGA) status at birth, independent of gestational age, is a determinant of poor postnatal linear growth. Promotion of institutional deliveries, exclusive breastfeeding, and prevention and early treatment of pneumonia may be helpful to improve linear growth in SGA-LBW infants during early infancy. Clinical Trial Registration [https://clinicaltrials.gov/], identifier [NCT02653534].